A prospective cross-sectional study on prescribing pattern of antibiotics on patients suffering from ENT infections in tertiary care hospital, Pokhara, Nepal - Gupta, Surendra P.; Poudel, Salikram; Gupta, Anil P.; Bashyal, Basanta; Baskota, Bishal; Sah, Anil K.; Pandaya, Subash; Shrestha, Dhiraj (International Journal of Basic & Clinical Pharmacology, 2017)
Background: This survey was designed to assess and evaluate the prescribing pattern of antibiotics used in patients suffering from ENT (Eye, Nose, and Throat) infections in ENT outpatient departments (OPD) at Manipal Teaching Hospital (MTH), Phulbari, Pokhara, Nepal. Methods: A prospective cross-sectional study was conducted in out-patients of ENT department at MTH for 6 month in which a total of 216 prescriptions were observed randomly and data filled patient profile forms were collected and analyzed. Results: Out of 216 patients, 126(58.33%) were male and 90 (41.67%) were female. Patients of age group 21-30 were maximum (29.16%) followed by age group of 11-20 (22.22%). Only 6.7% of drugs were prescribed from their generic names. Data analysis revealed that about 72.24%, 24.53% and 3.23% of prescription contained one, two and three antibiotic drugs respectively. All together 970 drugs were prescribed in 216 prescriptions out of which 251 (25.87%) were antibiotics drugs. This suggested that the average no. of antibiotics per prescription was 1.16. Among prescribed antibiotics, Amoxicillin (7.56%) of penicillin group, Azithromycin (8.36%) of macrolides, Cefuroxime (9.56%) of 2nd generation cephalosporin followed by Cefpodoxime (32.27%) of 3rd generation cephalosporin and Ofloxacin (6.37%) of quinolones group were frequently prescribed. From analysis, we found that other concomitant medications were also prescribed such analgesics, antihistamines, PPI (Proton Pump Inhibitors) and vitamins, minerals and dietary enzymes. The prescribed antibiotics accounted for large percentage of oral dosage forms (89.90%) followed parental injection dosage forms 5.05%. Conclusions: Prescribing more than one antibiotics was commonly encountered indicating the occurrence of polypharmacy which were based on empirical therapy without any culture and sensitivity test report. Therefore, local hospital culture sensitivity database for ENT infections has to be developed and prescribing with generic name from existing essential drug list or formulary should be encouraged for rational drug therapy.